BLteae ERASMUS + Programme Local Dissemination Project - Chan, Margaret (UiTM Sarawak, 2020)
The BLteae Local Dissemination Project was an off shoot of the Blended Learning (BL) Training for Teachers Educators between Europe and Asia (BLTeae) funded by the European Union (574130-EPP-1-2016-1-FR-EPPKA2-CBHE-JP). The consortium consolidated various competence skill practices in blended learning towards common elements and developed the Blended Learning courseware with modules related to pedagological innovative practices and education technology as international Massive Open Online Course (MOOC) courses. The UiTM team of Associate Professor Dr. Margaret Chan, the national coordinator, Associate Professor Dr. Ling Siew Eng, Ling Siew Ching and Adeline Engkamat developed the module on Social Media in Teaching.